An ionic-based carbon dot for enantioselective discrimination of nonaromatic amino alcohols. Issue 9 (2nd April 2020) - Wu, Datong; Pan, Fei; Gao, Li; Tao, Yongxin; Kong, Yong
Abstract : An ionic chiral carbon dot was designed and synthesized for the chiral recognition of nonaromatic amino alcohols. Abstract : Here, ionized chiral carbon dots, ( S, S )-C-dots-1 ( λ ex = 430 nm, λ em = 480 nm), were synthesized via a facile route with relatively high quantum yield (∼24.4%) and used as a fluorescent chiral sensor. One of the advantages of the synthetic process is that it avoids the loss of the chiral center. That is, the chiral bromo compound can directly form an ionic pair with the pyridyl group, which is derived from the amine precursor in the first step. Furthermore, ( S, S )-C-dots-1 shows clear discrimination toward different configurations of nonaromatic amino alcohols in the presence of Cu(ii ). When the ( R )-isomer is added to a solution of ( S, S )-C-dots-1 + Cu(ii ), it shows much higher fluorescent intensity than the ( S )-isomer. The values of I R / I S are 2.9 and 2.3 for 2-aminobutan-1-ol and 2-aminopropan-1-ol, respectively. In summary, we believe that this work can expand the synthetic routes and potential applications of functional carbon dots in the field of enantioselective sensing.